Dataset for "Cell surface remodeling caused by the loss of the flippase subunit TMEM30A in immune cells" - Sezgin, Erdinc; Gürdap, Cenk; Ragaller, Franziska; Muller, Marion; Sjule, Ellen; Sych, Taras; Blomen, Linnea; Thoren, Fredrik; Levental, Ilya; Levental, Kandice R.; J Sattentau, Quentin (Karolinska Institutet, 2026)
It contains data sets from the publication Gurdap and Ragaller et al, 2026, Journal of Cell Science (DOI: TBD).

with the details for citation provided in the README file.

Please cite this item as:

Cenk O. Gurdap, Franziska Ragaller, Marion Muller, Ellen Sjule, Taras Sych, Linnea Blomén, Fredrik Thoren, Ilya Levental, Kandice R. Levental, Quentin Sattentau, Erdinc Sezgin

DOI: 10.17044/scilifelab.32991887

It contains microscopy excel sheets of the data.

Abstract

Plasma membrane lipid asymmetry is tightly regulated and fundamental to mammalian cell physiology. TMEM30A is the β‑subunit of P4‑ATPases, flippase enzymes that maintain strict phosphatidylserine (PS) asymmetry by pumping it from the outer to the cytosolic leaflet. Loss of TMEM30A function causes constitutive PS externalization and has been implicated in diseases such as diffuse large B‑cell lymphoma and tumour immune evasion. Here, we systematically define the biophysical and molecular consequences of TMEM30A deletion in immune cells. Using a live‑cell lipid reporter, membrane order probe, and surface proteome mapping, we show that TMEM30A‑knockout cells display robust PS externalization accompanied by faster lateral diffusion of membrane constituents and decreased plasma membrane order. Surface proteome reorganization includes increased abundance of tetraspanins and CD47. Further, TMEM30A loss triggers glycocalyx remodeling via ADAM10‑dependent shedding that removes major transmembrane mucins, including CD43 and CD162. Together, these data reveal a coordinated reorganization of lipids, glycans, and proteins upon TMEM30A loss, suggesting mechanistic links between flippase dysfunction and increased plasma membrane dynamics and potential sensitization to immune therapy. Furthermore, our study provides an integrated surfaceome framework that might shed light on the relationship between TMEM30A expression and clinical outcomes in cancer.

Data usage

Researchers are welcome to use the data contained in the dataset for any projects. Please cite this item upon use or when published. We encourage reuse using the same CC BY 4.0 License.

Data Content

Excel files for graphs

Software to open files

.csv - Microsoft excel
Keywords: Receptors and membrane biology; Medical and Health Sciences; Medicin och hälsovetenskap; Biological Sciences; Biologi